2023
DOI: 10.7759/cureus.34816
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge and Practices Related to Foreign Body Aspiration in Children in Makkah, Saudi Arabia

Abstract: BackgroundForeign body aspiration (FBA) is a life-threatening event and one of the most common causes of mortality in children. As it has different clinical presentations, parental knowledge is essential for early management to prevent complications. ObjectivesThis study was designed to assess the knowledge and practices relating to FBA in children among parents living in Makkah city, Saudi Arabia. MethodsAn online questionnaire was designed using Google Forms (Google LLC, Mountain View, California, United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These findings align with the outcomes of three related studies conducted in both Turkey and Saudi Arabia, emphasizing the existence of elevated knowledge levels among individuals with higher educational backgrounds. 25 , 26 , 29 Nevertheless, it is important to acknowledge that a study conducted in Dammam city, Saudi Arabia, did not identify any substantial disparities in choking-related knowledge between participants who had completed high school and those who had attained a college-level education. 28 …”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These findings align with the outcomes of three related studies conducted in both Turkey and Saudi Arabia, emphasizing the existence of elevated knowledge levels among individuals with higher educational backgrounds. 25 , 26 , 29 Nevertheless, it is important to acknowledge that a study conducted in Dammam city, Saudi Arabia, did not identify any substantial disparities in choking-related knowledge between participants who had completed high school and those who had attained a college-level education. 28 …”
Section: Discussionmentioning
confidence: 98%
“… 23 , 25 Conversely, investigations targeting parents in the Al Qassim region and Makkah city have indicated that females displayed heightened levels of knowledge in this domain. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations